Quality of Education in Islamic Schools: A Bibliometric Review Study - Nur Ifani, Nadia; Putri Kartiwi, Asti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
For decades, the state of education in Muslim-majority countries has garnered worldwide attention. This literature study was conducted using a bibliometric analysis method adapted from the VOSviewer software to examine the literature on the quality of Islamic education. Data from 500 studies related to this topic were sourced from the Web of Science, spanning the years from 2000 to 2018. The results of the analysis were presented and discussed using various approaches, including authors, keywords, references (cited research articles), types of research work, countries of origin, and research institutions. The research findings indicate that bibliometric analysis proves to be an effective means of elucidating the theoretical foundations within the literature and constructing a comprehensive theoretical framework regarding the quality of Islamic education. Consequently, this study offers valuable recommendations based on the literature review